Analisis Kelayakan Bisnis dan Strategi Operasional Start-Up Fashion Travel-Wear: Studi Kasus TRAVRL - Aziz Muhammad Rizqi; Hani Humaeriyah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to conduct an in-depth evaluation and comprehensive analysis of the business feasibility study of the fashion start-up "TRAVRL," an innovative business entity focused on the niche market of functional travel-wear products in Indonesia. The urgency of this research is based on the phenomenon of increased mobility of urban communities post-pandemic, which has triggered a shift in consumption preferences towards efficient yet aesthetic products. TRAVRL presents a strategic solution that integrates premium aesthetic value with practical features through the use of innovative Bamboo Essence materials. The feasibility analysis in this study was conducted through a holistic, multidimensional approach, covering market and marketing aspects, technical and production technology, human resource management, socio-economic, legal aspects, and financial aspects. The research methodology used a quantitative descriptive approach with primary data collection techniques through a structured questionnaire to 22 potential respondents. The results revealed a very significant level of market validation, where 90.9% of respondents confirmed the need for space-saving features and innovative material quality. Financially, this business unit demonstrated healthy performance with an average gross profit margin of 47.5% and a projected payback period of between 3 and 5 months. A synthesis of all aspects indicates that the TRAVRL business model is highly feasible for implementation in the national creative industry.